Influence of neutralization attitude in academic dishonesty among undergraduates - Chan, Ling Meng; Othman, Jamilah; D’Silva, Jeffrey Lawrence; Omar, Zoharah (Canadian Center of Science and Education, 2014)
Previous literature had proposed that individuals tend to use neutralization to motivate their decisions to engage in deviant behaviors. This indicated that even though students have strong motivations not to cheat may do so anyway after employing neutralizing strategies. Hence, this study attempted to examine the role of neutralization in influencing students’ attitude towards academic dishonesty. Students tend to use neutralization technique in order to free themselves from feeling guilty in engaging academic dishonesty. Besides that, it also attempted to study the reasons behind college student academic cheating behaviors. This study employed 620 randomly selected students from six different academic institutions. Results supported that students who engaged in academic dishonesty differ significantly from those who did not engage in this deviant behaviour with respect to their tendency to neutralize cheating. Results showed that cheating and neutralization were positively correlated among students. Through the findings, it showed that the use of neutralization techniques explained why students acknowledged that cheating is wrong but still chose to do it anyway.